Cooking with confidence for autistic youth: outcomes from a pilot program evaluation model - Mi-Yeet Wong; Conner Carlton; Shelby Paul; Jonathan Deutsch; Rachel Sherman; Brandy-Joe Milliron; Nicole Farmer; Rachel Hingst; Claire Richardson; Lindsay Shea (BMC Research Notes)
Abstract Objective This article outlines the evaluation model for the Cooking with Confidence (CWC) program, developed using Bandura’s Social Learning Theory as its conceptual framework. The evaluation aimed to: (1) Examine participant characteristics in the CWC program, (2) Assess changes in cooking knowledge, skill acquisition, self-efficacy, and confidence, and (3) Identify barriers and facilitators to participant engagement. CWC is a community-based educational program designed to help autistic young adults develop independent living skills and promote health through hands-on cooking classes. Recognizing the need for more opportunities for autistic individuals to practice these skills, the program was created through public and private partnerships. A pre-post study design was employed, with participants completing surveys before and after their involvement in the program. Results Participants reported high satisfaction with the program and showed improvements in cooking knowledge and self-efficacy. The analysis also highlighted participant characteristics, as well as key barriers and facilitators to cooking. Overall, the CWC program demonstrated positive outcomes, with findings offering valuable insights for future program development to enhance its impact.